Distance walked and run as improved metrics over time-based energy estimation in epidemiological studies and prevention; evidence from medication use. - Paul T Williams (Public Library of Science (PLoS), 2012)
Purpose The guideline physical activity levels are prescribed in terms of time, frequency, and intensity (e.g., 30 minutes brisk walking, five days a week or its energy equivalence) and assume that different activities may be combined to meet targeted goals (exchangeability premise). Habitual runners and walkers may quantify exercise in terms of distance (km/day), and for them, the relationship between activity dose and health benefits may be better assessed in terms of distance rather than time. Analyses were therefore performed to test: 1) whether time-based or distance-based estimates of energy expenditure provide the best metric for relating running and walking to hypertensive, high cholesterol, and diabetes medication use (conditions known to be diminished by exercise), and 2) the exchangeability premise. Methods Logistic regression analyses of medication use (dependent variable) vs. metabolic equivalent hours per day (METhr/d) of running, walking and other exercise (independent variables) using cross-sectional data from the National Runners' (17,201 male, 16,173 female) and Walkers' Health Studies (3,434 male, 12,384 female). Results Estimated METhr/d of running and walking activity were 38% and 31% greater, respectively, when calculated from self-reported time than distance in men, and 43% and 37% greater in women, respectively. Percent reductions in the odds for hypertension and high cholesterol medication use per METhr/d run or per METhr/d walked were ≥ 2-fold greater when estimated from reported distance (km/wk) than from time (hr/wk). The per METhr/d odds reduction was significantly greater for the distance- than the time-based estimate for hypertension (runners: P<10(-5) for males and P=0.003 for females; walkers: P=0.03 for males and P<10(-4) for females), high cholesterol medication use in runners (P<10(-4) for males and P=0.02 for females) and male walkers (P=0.01 for males and P=0.08 for females) and for diabetes medication use in male runners (P<10(-3)). Conclusions Although causality between greater exercise and lower prevalence of hypertension, high cholesterol and diabetes cannot be inferred from these cross-sectional data, the results do suggest that distance-based estimates of METhr/d run or walked provide superior metrics for epidemiological analyses to their traditional time-based estimates.